PENGARUH CORPORATE GOVERNANCE, KEBIJAKAN DIVIDEN, STRUKTUR MODAL, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Putri Natalee, Merry Susanti (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to determine whether corporate governance, dividend policy, capital strcture, and profitability affect the firm value. There are 136 non-financial firms which were used as samples in this research and obtained by purposive sampling technique. The data was processed by EViews9. The results from the t test show that capital structure has positive and significant effect towards firm value. Nevertheless, corporate governance, dividend policy and profitability do not affect firm value.